The burden of the minimum wage : evidence from Portugal - Teixeira, Tiago Fernandes (2020)
This thesis examines the elasticity of employment and wages to changes in the minimum wage and the incidence of the costs of these changes between consumers and firm owners, using firm-level financial information linked to longitudinal employer-employee data from Portugal between 2008 and 2017. It exploits differences in firm exposure to changes in the minimum wage to uncover the sensitivity of employment and wages to this policy and the main margins of adjustment of firms. It finds that more exposed firms experience higher growth in average wage and a larger decline in employment. The employment elasticities with respect to average wages range from -0.48 to -0.56 over 2008–17. Subperiod analysis shows that the employment elasticity varies considerably, with the increases in the minimum wage resulting in larger negative effects on employment during the crisis period of 2010 to 2014, when firms were arguably less able to transfer the burden to consumers in the form of higher prices. During this period, the employment elasticity was -0.77. In terms of incidence, during the period of positive growth (2008–09), the increase in the margin between revenues and materials suggests that most of the costs of the minimum wage increases were borne by consumers. In the subsequent periods, the majority of the minimum wage costs was borne by firm owners, as firms suffer a decrease in profits that offset the increase in labor costs caused by the higher minimum wage.